Effects of APOE ε2 allele on basal forebrain functional connectivity in mild cognitive impairment. (5th December 2022) - Liu, Xiaocao; Zeng, Qingze; Luo, Xiao; Li, Kaicheng; Xu, Xiaopei; Hong, Luwei; Li, Jixuan; Guan, Xiaojun; Xu, Xiaojun; Huang, Peiyu; Zhang, Min‐Ming; ,
Abstract: Background: Basal forebrain cholinergic system (BFCS) dysfunction is associated with cognitive decline in Alzheimer's disease (AD) and mild cognitive impairment (MCI). Apolipoprotein E ( APOE ) ε2 is a protective genetic factor in AD and MCI, and cholinergic sprouting depends on APOE . Objective: We investigated the effect of the APOE ε2 allele on BFCS functional connectivity (FC) in cognitively normal (CN) subjects and MCI patients. Method: We included 60 MCI patients with APOE ε3/ε3, 18 MCI patients with APOE ε2/ε3, 73 CN subjects with APOE ε3/ε3, and 36 CN subjects with APOE ε2/ε3 genotypes who had resting‐state functional magnetic resonance imaging data from the Alzheimer's disease Neuroimaging Initiative. We used BFCS subregions (Ch1‐3 and Ch4) as seeds and calculated the FC with other brain areas. Using a mixed‐effect analysis, we explored the interaction effects of APOE ε2 allele × cognitive status on BFCS‐FC. Furthermore, we examined the relationships between imaging metrics, cognitive abilities, and AD pathology markers, controlling for sex, age, and education as covariates. Results: An interaction effect on functional connectivity was found between the right Ch4 (RCh4) and left insula ( p < 0.05, corrected), and between the RCh4 and left Rolandic operculum ( p < 0.05, corrected). Among all subjects and APOE ε2 carriers, RCh4‐left Insula FC was associated with early tau deposition. Furthermore, no correlation was found between imaging metrics and amyloid burden. Among all subjects and APOE ε2 carriers, FC metrics were associated with cognitive performance. Conclusion: The APOE ε2 genotype may play a protective role during BFCS degeneration in MCI. Abstract : This article showed the evidence that the APOE ε2 allele impacts the FC patterns of basal forebrain cholinergic system (BFCS) subregions in MCI, which may be one of the important mechanisms contributing to its protective role. Furthermore, the APOE ε2 allele is associated with lower Tau deposition in BFCS subregions. The article might provide original insights for understanding the possible protection of APOE ε2 alleles in MCI patients.